Socialization of a Personality in Rural and Mountainous Conditions in the Context of Professional Education - Mokanyuk, Yulianna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article discusses the features of socialization in education and educational environment in rural and mountain schools. The author analyzes the characteristics of vocational guidance for adolescents; components of career guidance in schools in rural and mountainous areas. The author believes that the need to create and implement proactive forms and technologies to learn. It is primarily about school degree, since it is in the high school age formed the basis of social identity formation. This motivated the study of the methodological aspects of the education of pupils in schools in rural and mountainous areas. Targeting high school students for professional work in general secondary education system needs rethinking science, the result of which should be the introduction of educational practice new meaning of educational work, new forms of career guidance. Before modern rural and mountain schools acute problem enhance career guidance activities. The main content of professional orientation of young people in rural areas is to cultivate students' professional interests to sustainable agriculture in the daily academic and extracurricular activities. In this connection it is necessary to start adequate training for innovative development of rural and mountainous areas in need of systematic approach to training process that involves complex requirements, which form a system of nature.